The role of PI3K/Akt signaling pathway in non-physiological shear stress-induced platelet activation - Chen, Zengsheng (Artif Organs, 2019)
The PI3K/Akt signaling pathway has been implicated in playing an important role in platelet activation during hemostasis and thrombosis involving platelet-matrix interaction and platelet aggregation. Its role in non-physiological shear stress (NPSS)-induced platelet activation relevant to high-shear blood contacting medical devices (BCMDs) is unclear. In the context of blood cells flowing in BCMDs, platelets are subjected to NPSS (>100 Pa) with very short exposure time (<1 sec). In this study, we investigated whether NPSS with short exposure time induces platelet activation through PI3K/Akt signaling pathway. Healthy donor blood treated with or without PI3K inhibitor was subjected to NPSS (150 Pa) with short exposure time (0.5 sec). Platelet activation indicated by the surface P-selectin expression and activated glycoprotein (GP) IIb/IIIa was quantified using flow cytometry. The phosphorylation of Akt, activation of the PI3K signaling, was characterized by western blotting. Changes in adhesion behavior of NPSS-sheared platelets on fibrinogen, collagen and von Willebrand factor (vWF) was quantified with fluorescent microscopy by perfusing the NPSS-sheared and PI3K inhibitor treated blood through fibrinogen, collagen and vWF-coated microcapillary tubes. The results showed that the PI3K/Akt signaling was involved with both NPSS-induced platelet activation and platelet-matrix interaction. NPSS-sheared platelets exhibited exacerbated platelet adhesion on fibrinogen, but had diminished platelet adhesion on collagen and vWF. The inhibition of PI3K signaling reduced P-selectin expression and GPIIb/IIIa activation with suppressed Akt phosphorylation and abolished NPSS-enhanced platelet adhesion on fibrinogen in NPSS-sheared blood. The inhibition of PI3K signaling can attenuate the adhesion of unsheared platelets (baseline) on collagen and vWF, while had no impact on adhesion of NPSS-sheared platelets on collagen and vWF. This study confirmed the important role of PI3K/Akt signaling pathway in NPSS-induced platelet activation. The finding of study suggests that blocking PI3K/Akt signaling pathway could be a potential method to treat thrombosis in patients implanted with BCMDs